Psychometric properties of the Body Checking Questionnaire in college women. (March 2015) - White, Emily K.; Claudat, Kim; Jones, Sarah C.; Barchard, Kimberly A.; Warren, Cortney S.
Highlights: Found two-factor structure of Body Checking Questionnaire (BCQ) in college women. Factor structure differed from both original and recent factor analyses. Two-factor solution demonstrated good validity, reliability, and sensitivity. Research on the number and nature of factors underlying the BCQ remains mixed. Abstract: While the Body Checking Questionnaire (BCQ;Reas et al., 2002 ) is the most commonly-used measure of body checking behaviors, findings on the factor structure in nonclinical samples are mixed. This study investigated the factor structure and psychometric properties of the BCQ among nonclinical college women. In Study 1 ( n = 326), an exploratory factor analysis indicated factors corresponding to (a) behavioral and (b) visual checking. In Study 2 ( n = 1013), a confirmatory factor analysis revealed adequate fit for these factors, better than the original or total score solutions. Scales based upon the two factors demonstrated good internal consistency, convergent validity with measures of eating pathology, and sensitivity for detecting at-risk eating pathology. Results suggest an alternate two-factor solution that differs from the original three-factor solution.